2011
DOI: 10.1016/j.jbiomech.2010.12.028
|View full text |Cite
|
Sign up to set email alerts
|

Computed-tomography-based finite-element models of long bones can accurately capture strain response to bending and torsion

Abstract: Finite element (FE) models of long bones constructed from computed-tomography (CT) data are emerging as an invaluable tool in the field of bone biomechanics. However, the performance of such FE models is highly dependent on the accurate capture of geometry and appropriate assignment of material properties. In this study, a combined numerical-experimental study is performed comparing FE-predicted surface strains with strain-gauge measurements. Thirty-six major, cadaveric, long bones (humerus, radius, femur and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 18 publications
2
46
0
1
Order By: Relevance
“…The elastic moduli for early isotropic models have been homogeneous (171)(172)(173), but more recent studies have used inhomogeneous materials (8,164,165,170,174-178) as they have been found to be more accurate than the models using homogeneous material properties (9,179,180). For inhomogeneous material properties, the elastic modulus is typically estimated using empirical equations that relate the bone density to modulus.…”
Section: The Finite Element Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The elastic moduli for early isotropic models have been homogeneous (171)(172)(173), but more recent studies have used inhomogeneous materials (8,164,165,170,174-178) as they have been found to be more accurate than the models using homogeneous material properties (9,179,180). For inhomogeneous material properties, the elastic modulus is typically estimated using empirical equations that relate the bone density to modulus.…”
Section: The Finite Element Methodsmentioning
confidence: 99%
“…Density-elasticity relationships have also been developed using optimization techniques for the human femur (8,194,195), tibia (8,196), humerus (8), radius (8), and ulna (197).…”
Section: The Finite Element Methodsmentioning
confidence: 99%
See 3 more Smart Citations